UPAYA MENINGKATKAN HASIL BELAJAR BIOLOGI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) PADA MATERI VIRUS DI KELAS X MIPA-2 SMA NEGERI 1 KEUMALA - Jufri Jufri (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
This study aims to find out: (1) how to apply the numbered head together (NHT) type cooperative learning model in learning biology subject matter Viruses in class X MIPA-2 SMA Negeri 1 Keumala, Pidie Regency in the2021/2022 academic year, (2) how much The numbered head together (NHT) type of cooperative learning model is able to improve the biology learning outcomes of the subject matter of viruses in class X MIPA-2 SMA Negeri 1 Keumala, Pidie Regency, in the 2021/2022 academic year. This research is a Classroom Action Research (CAR). In this study, the researcher used one class to apply the numbered head together (NHT) type of cooperative learning model, namely class X MIPA2 SMA Negeri 1 Keumala, Pidie Regency, which consisted of 35 students. When the NHT type of cooperative learning is implemented, the learning atmosphere in class X.MIPA2 becomes more lively, students become more active and learning outcomes are maximized. This research was carried out in three stages, the first stage was a pre-cycle activity, namely looking for data on student learning outcomesin class X MIPA2 the previous year. This is important as the basis for the initial value. The second stage is the implementation of cycle I, cycle II and cycle III. While the third stage is data refinement and report preparation. In the initial conditions before the NHT type cooperative learning model was applied, student learning outcomes were very low, namely the average learning outcome was only 61.36 with learning completeness of 25.5%. After implementing the NHT cooperative learning model, students' activities and learning outcomes increased. In the first cycle, the percentage of learning activities among students was 57,14% with an average student learning outcome of 69.3 and 31.42% of learning completeness or 11 students. In cycle II, the percentage of learning activities among students was 80.47% with an average learning outcome of 79.37 and learning completeness of 71.42% as many as 25 students who completed. While in the third cycle, the percentage of learning activities among students was 87.38% with an average learning outcome of 86.03 and learning completeness of 94.28% as many as 33 students completed. From these data, it is clear that there is an increase in learning activities and learning outcomes from before the implementation of the NHT type cooperative learning model to after the learning model was implemented.Keywords: Numbered head together (NHT) learning model, learning outcomes